2017
DOI: 10.1177/1403494817705559
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment and menstrual disorders among Italian university women: A cross-sectional observational study

Abstract: Sexual harassment is related to the prevalence of menstrual disorders. Healthcare providers should encourage dialogue with patients and address the issue of sexual violence or harassment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
4
10
1
2
Order By: Relevance
“…The current estimates of sexual harassment are comparable with the review by Fedina et al ,7 who synthesised research in the field from the last 15 years, concluding that although prevalence rates vary, they all indicate that a substantial number of college and university students experience sexual harassment. In line with that review, as well as estimates from European universities,14 15 we also found that unwanted sexual contact and verbal sexual harassment were the most prevalent forms, both being reported by approximately 15% of the students (20%–21% of women and 4%–5% of men). In terms of lifetime rape and rape attempt, this was reported by 3.4% and 2.1%, respectively, whereas the past year prevalences were around 0.4%.…”
Section: Discussionsupporting
confidence: 90%
“…The current estimates of sexual harassment are comparable with the review by Fedina et al ,7 who synthesised research in the field from the last 15 years, concluding that although prevalence rates vary, they all indicate that a substantial number of college and university students experience sexual harassment. In line with that review, as well as estimates from European universities,14 15 we also found that unwanted sexual contact and verbal sexual harassment were the most prevalent forms, both being reported by approximately 15% of the students (20%–21% of women and 4%–5% of men). In terms of lifetime rape and rape attempt, this was reported by 3.4% and 2.1%, respectively, whereas the past year prevalences were around 0.4%.…”
Section: Discussionsupporting
confidence: 90%
“…However, unlike most of the others' study ndings of WSH's consequences in the hospitality workplaces, the reproductive health-related effects other than transactional sex practice and engagement in commercial sex work, menstrual disorders, and acquiring STIs, including HIV/AIDS, were reported in this study. The menstrual disorder issue as an effect of WSH is consistent with a quantitative study nding among female Italian university students [72]. This nding is unique and not well-addressed in WSH literature.…”
Section: Discussionsupporting
confidence: 87%
“…However, unlike most of the others' study ndings of the consequences of SH in the hospitality workplaces, the reproductive health-related effects other than transactional sex practice and engagement in commercial sex work, menstrual disorders, and acquiring STIs, including HIV/AIDS, was reported in this study. The issue of the menstrual disorder as an effect of SH is consistent with a quantitative study nding among female Italian university students [74]. This nding is unique and not well addresses in workplace sexual harassment literature.…”
Section: Discussionsupporting
confidence: 80%